x=ori
a).11x(-2)+(-4)x[-100-4x(-26)]=
Răspunsuri la întrebare
Răspuns de
1
iti dau direct rezolvarea:
=11x+6x[-100-4x(-26)]=
=11x+6x+4x[-100-26]=
=21x-126
=11x+6x[-100-4x(-26)]=
=11x+6x+4x[-100-26]=
=21x-126
Răspuns de
2
11×(-2)+(-4)×[-100-4×(-26)]=
-22+(-4)×[-100-(-104)]=
-22+(-4)×4=
-22+(-16)=-38
-22+(-4)×[-100-(-104)]=
-22+(-4)×4=
-22+(-16)=-38
Alte întrebări interesante
Matematică,
9 ani în urmă
Franceza,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă
Biologie,
10 ani în urmă